2009
DOI: 10.1111/j.1440-1797.2008.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D deficiency in north Indian adults is exacerbated in those with chronic kidney disease

Abstract: Vitamin D deficiency is highly prevalent in north Indians, and this is more pronounced in CKD subjects. There is a significant inverse correlation between the vitamin D and PTH levels. The clinical significance of this deficiency and the potential benefits to be derived from vitamin D supplementation in this population merits further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…A high prevalence of vitamin D insufficiency has been found in all ages in northern India [1,5]. The 25OHD levels were not readily available at our hospital and were carried out at one instance for patients as a part of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of vitamin D insufficiency has been found in all ages in northern India [1,5]. The 25OHD levels were not readily available at our hospital and were carried out at one instance for patients as a part of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic kidney disease (CKD) are much more likely to have low levels of 25OHD due to decreased exposure to sunlight, low endogenous synthesis of vitamin D 3 in the skin and reduced intake of foods that are natural sources of vitamin D [4]. Whereas a recent study showed that 99% of adults with CKD 4-5 in north India had vitamin D insufficiency [5], similar estimates are unknown for children with CKD.…”
Section: Introductionmentioning
confidence: 97%
“…Evidence has not favored the association between hypoalbuminemia and other endocrine abnormalities in CKD [18]. However, hypoalbuminemia in patients with CKD is an independent risk factor for cardiovascular mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…8 Evidence has not favored the association between hypoalbuminemia and other endocrine abnormalities in CKD. 9 However, hypoalbuminemia in patients with CKD is an independent risk factor for cardiovascular mortality. 10 There have been controversies as to whether SCH in ESRD warrants thyroxine supplementation.…”
Section: Discussionmentioning
confidence: 99%